Cartilage Imaging: Techniques and Developments - Oei, Edwin H.G.; Wick, Marius C.; Müller-Lutz, Anja; Schleich, Christoph; Miese, Falk R. (Seminars in Musculoskeletal Radiology, 2018)
Cartilage degeneration is one of the most common chronic age-related joint disorders leading to pain and reduced joint motion. The increasing prevalence of osteoarthritis requires accurate cartilage imaging, both clinically and in research. Detailed cartilage imaging is also necessary for traumatic cartilage lesions and for pre- and postoperative assessment of cartilage repair procedures. Although still widely used, conventional radiography bears significant limitations because it assesses cartilage indirectly by joint space width. Magnetic resonance imaging (MRI) enables direct visualization of cartilage damage along with other concomitantly affected joint tissues. Several semiquantitative grading systems and volumetric analysis methods exist to assess cartilage damage and cartilage repair on MRI. Quantification of hyaline and fibrocartilage biochemical composition is possible with novel MRI methods such as T2- and T1ρ-mapping, delayed gadolinium-enhanced MRI of cartilage, glycosaminoglycan chemical exchange saturation transfer, and sodium imaging, along with quantitative computed tomography arthrography. These techniques provide promising quantitative imaging biomarkers that can detect early cartilage changes before morphological alterations occur.
Keywords: articular cartilage; imaging; radiography; magnetic resonance imaging; computed tomography